In which journals do family and community physicians in Brazil publish? - Leonardo Fontenelle; Miguel Henrique Moraes de Oliveira; Stephani Vogt Rossi; Diego José Brandão; Thiago Dias Sarti (Sociedade Brasileira de Medicina de Família e Comunidade, 2021)
Introduction: Authors choose scholarly journals not only to advance their careers but also to interact with their respective scholarly communities. Objective: To describe the journals where family and community physicians in Brazil publish their work. Methods: In late 2018, we compiled a nationwide list of family and community physicians, and downloaded their curricula from the Lattes Platform. We extracted data on their complete journal articles from their curricula, completed these data with queries to CrossRef, VHL/LILACS, and PubMed/MEDLINE, and obtained data on the journals with queries to the United States NLM Catalog. Results: We found 3558 unique articles, published by 1011 journals. The most productive journal was RBMFC (Revista Brasileira de Medicina de Família e Comunidade), which published 347 (9.8%) of these articles. About one in six articles were published in journals on family practice or primary health care. The proportion of articles published in journals in Brazil decreased during the study period from 83.8% to 58.4%. Conclusion: As in other countries, family and community physicians in Brazil usually publish in the national journal dedicated to their scholarly community, while also publishing extensively in journals from other disciplines. The increasing proportion of articles published in journals outside Brazil suggests primary care research in Brazil is increasingly of international relevance.